Equity and Influencing Factors of Health Service Utilization among Middle-aged and Elderly Adults with Disabilities in Rural Mountainous Areas of Southern Ningxia During 10 Years after the New Healthcare Reform - WANG Wenlong, GAO Baokai, HU Zhaoyan, CHEN Kexin, QIAO Hui (Zhongguo quanke yixue, 2023)
Background As global aging advances, the number of people with disability is increasing. Disability seriously affects quality of life and increases the burden caused by healthcare expenditure. Most domestic studies focus on disabilities in middle-aged and elderly people, but there is a lack of longitudinal studies on the fairness of health service utilization and changes in its associated factors in rural middle-aged and elderly people with disability. Objective To analyze the fairness of health service utilization and major associated factors in middle-aged and elderly people with disability in rural mountainous areas of southern Ningxia. Methods This study used data from three waves of the Rural Household Health Survey (including the baseline survey in 2009 and two follow-up surveys in 2015 and 2019), and selected middle-aged and elderly adults (≥55 years old) with disabilities from the surveyees as the participants. The health service utilization equity of sample population before the new healthcare reform launched in 2009 and during 10 years after the reform was analyzed by using concentration index, and factors affecting the equity were analyzed by decomposing the concentration index. Results We selected 1 351 cases from the surveyees of 2009, 1 521 cases from the surveyees of 2015, and 685 cases from the surveyees of 2019. The concentration index for two-week visit rate in the participants was 0.119 9 for 2009, 0.052 1 for 2015, and 0.060 9for 2019. Women (CI=0.108 2, -0.084 1) had higher level of inequalities in heath service utilization than men (CI=-0.022 9, 0.029 5) in 2015, 2019 year. Upper-middle income and high income were major factors contributing to inequalities in health service utilization in this population in 2009, explaining 3.626 9% and 2.596 5% of the inequalities, respectively. In 2015, in addition to economic factors, marital status (married), degree of education (primary) and household size (moderate) were another major factor contributing to inequalities in health service utilization, explaining 0.478 6%、0.398 4%、-0.339 2% of the inequalities, respectively. And in 2019, besides economic factors, household size (advanced) and Age (70-74 years old) were major factor contributing to inequalities in health service utilization, explaining -0.953 4%、0.694 3% of the inequalities, respectively. Conclusion Rich-related inequalities were found in the use of care for an ill within two weeks in this group of people, in Ningxia the past decade of the new medical reform. The main influencing factors of equity gradually evolved from the relatively single phenomenon of economic income being the dominant factor to the situation where age, household size, economic income, and other factors interact in multiple ways. Moreover, the strength of association age, vocational type inequalities in health service utilization in women was greater than that in men.